2011
DOI: 10.4293/108680811x13125733356594
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Paraesophageal Hernia Repair with Acellular Dermal Matrix Cruroplasty

Abstract: This study suggests that laparoscopic paraesophageal hernia repair with acellular dermal matrix Cruroplasty is an effective method of repairing symptomatic paraesophageal hernias with a low perioperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
(27 reference statements)
0
16
0
1
Order By: Relevance
“…Interestingly, this recent study shows a very high recurrence rate (54–59%) for both groups . Other studies have shown benefit of using an absorbable, biologic mesh to buttress the repair of large (>5 cm) hiatal hernias …”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Interestingly, this recent study shows a very high recurrence rate (54–59%) for both groups . Other studies have shown benefit of using an absorbable, biologic mesh to buttress the repair of large (>5 cm) hiatal hernias …”
Section: Introductionmentioning
confidence: 69%
“…All patients completed a preoperative symptom score questionnaire recording esophageal and throat complaints of chest pain, heartburn, regurgitation, dysphagia, aspiration, and hoarseness which has been developed and validated by multiple authors. [20][21][22][24][25][26][27][28] They were asked to grade the frequency of symptoms on the following scale: 0 = never, 1 = once/month, 2 = once/week, 3 = daily, 4 = several times daily. For values between two data points, score was assigned to the higher value.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wisbach [26] found 1 radiologic recurrence in 11 patients having paraesophageal hernia repair with allograft at mean 1-year follow-up. Diaz [27] found 2/46 symptomatic recurrences, and 2/26 radiologic recurrences, in patients undergoing paraesophageal hernia repair with allograft reinforcement (Allomax) with 3.6-month follow-up [27]. Of note, no erosions were observed in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Use of biologic materials, including acellular human dermis, has shown safe and effective results [10][11][12]. However, direct comparative studies evaluating biologic reinforcement do not exist.…”
mentioning
confidence: 98%